Public art encounters - Palmer, Joni M.; Zebracki, Martin 1984- (Routledge, 2018)
1. On encountering public art / Martin Zebracki and Joni M. Palmer -- 2. Subverting surveillance: power and incivility in public transit art / Martha Radice and Brenden Harvey -- 3. 'Awaken the dragon': participatory art-making and the grassroots in authoritarian Singapore -- 4. The construction of post-communist ideologies and re-branding of Budapest: the case study of Statue Park Museum / Paul Clements -- 5. Sustainable influences of public art: a view on cultural capital and environmental impact / Cameron Cartiere and Ashley Guindon -- 6. Shaping subjects, connecting communities, imagining futures? Critically investigating Play Your Place / Harriet Hawkins and Ruth Catlow -- 7. The production of temporary public space: site-specific installation and 'vital materialities' / Gwen MacGregor -- 8. 'All your drains belong to us': young people and the non-representational geographies of public art in drain tunnels / Candice Boyd -- 9. Mobilising the 'Right to Remain' in Vancouver's Paueru-gai: an art based participatory research intervention / Aaron Franks, Jeff Masuda, Audrey Kobayashi and The Right to Remain community fair team -- 10. The art of (re)crossing the border: the Border Farm project in Maroi, South Africa / Pauline Guinard -- 11. The Birmingham Surrealist Laboratory: unlocking community and the avant-garde in a super diverse city / Saskia Warren and Stephen Forcer -- 12. A cybergeography of public art encounter: the case of Rubber Duck / Martin Zebracki -- 13. An artist-geographer's lens / Andrew Gorman-Murray.